Interaction between mycorrhizal fertilizers and varieties to increase organic patchouli production in the Entisol soil of Aceh Besar. Issue 1 (November 2021) - Syafruddin, S; Syakur, S; Saiful; Safrida; Sulaiman, I; Munandar, F A; Herlina, C N
Abstract: The purpose of this study was to determine the interaction effect of the use of mycorrhizal biofertilizers and varieties to increase the production of organic patchouli on the Entisol soil of Aceh Besar. This study used a factorial randomized block design with three replications. The first factor observed was mycorrhizal biofertilizer from the various genus, namely Glomus mosseae, Gigaspora sp. and the mixed genus of Glomus mosseae and Gigaspora sp. While the second factor is the use of varieties, namely Tapak Tuan and the Lhokseumawe variety. The results showed that the best interactions on the growth and production, P205 uptake, and oil content were found in the mixed mycorrhizal genus ( Glomus mosseae + Gigaspora sp.) with the Tapak Tuan variety. From the patchouli alcohol content test results, the best results were obtained in a combination of mixed mycorrhizal biofertilizers and the Tapak Tuan variety by 30%.